Reading comprehension and mathematical problem solving in students of a rural secondary educational institution in Peru (GnosisWisdom, 2025)
The study aimed to determine the degree of correlation between reading comprehension levels and mathematical problem solving in first-year secondary school students at a rural secondary school in Peru. The study used a basic, descriptive, correlational design in a sample of 77 students. The instruments were a reading comprehension test-type questionnaire, which collected information from the literal, inferential, and critical levels, adapted to the student's context with 10 closed-ended questions, and a second, a mathematical problem-solving test-type questionnaire, which was categorized according to interval ranges as low, average, and high. The results found in reading comprehension were that the low level represented the highest percentage of critical level comprehension at 79.2%, followed by inferential reading comprehension at 71.4%, and the lowest percentage represented literal reading comprehension at 3.9%. the average or regular level, in first place appears literal reading comprehension with 83.1%, followed by inferential reading comprehension with 22.1% and lastly in this category we have critical reading comprehension with 18.2% while the high level is observed to have reached the maximum percentage in literal reading comprehension with 13%, followed by percentages reached by inferential reading comprehension with 6.5%, finally, this category reached a minimum percentage in critical reading comprehension which represents 2.6%. The levels of mathematical problem solving corresponding to the students under study, it was obtained that 81.8% obtained failing scores (0 to 10) with a low level, 14.3%, scores of (11 to 15) with a regular level and a minority proportion, 3.9% at high level or passing scores of (16 to 20). With a median of 6 points, arithmetic mean of 6.67 and a standard deviation of +/- 3.44 points.
Keywords: Reading comprehension; mathematical problem solving; rural secondary school